The effect of lead shielding thickness in computed tomography of the head: a phantom study / Farida Aimi Mustapha - Mustapha, Farida Aimi (2015)
CT of the head is the most requested examination in CT scan. However, the routine use of external shielding in CT imaging appears to be limited. It is because of concern that the application of external lead shielding may result in increased internal scatter and consequently lead to an increased dose to the radio sensitive organs (Palmer, 2008). The purpose of this study is to investigate the effect of different thickness of lead shielding in computed tomography (CT) examination of the head. This research is an experimental study using an anthropomorphic Rando phantom to imitate the patient. Different thickness of thyroid shield was applied which are 0.0 mm Pb, 0.5 mm Pb, 1.0 mm Pb and 1.5 mm Pb to protect thyroid gland from scattered radiation. Four thermoluminescent detector (TLD) chips were placed at surface of thyroid gland and 1 cm depth within thyroid tissue upon slice 10 and slice 11 of phantom. The Rando phantom was placed on the Siemens Somatom Definition Flash Dual Source 128-slice CT scanner table and a CT head protocol was performed. Then TLDs were read to measure the surface dose and absorbed dose of thyroid gland using different thickness of lead shield. The data collected was analysed m measure the significant different radiation dose with various different thickness of lead shielding using statistical one way ANOVA. This study provides evidence that the effectiveness of lead shielding varied with their thickness respectively corresponding to thyroid dose due to scattered radiation. The highest dose reduction was achieved by 1.5 mm Pb thickness which is 57.48% at the surface, 55.77% at 1 cm depth within thyroid tissue, followed by 1.0mmPb result in 56.69% at surface, 50% at 1 an depth. The lowest dose reduction was achieved with 0.5 mm Pb is 52.76% at surface, 41.35% at 1 cm depth within thyroid tissue. This research suggested the application of thyroid shielding gives advantage especially to the paediatric patient and patients that require repetition CT examination because long term illness. This research has proven that reducing radiation dose to the patient because of scattered radiation by increasing the thickness of lead shielding can further decrease dose to radio sensitive organ outside the seaming area. As a result, the risks of inducing cancer will also be decreased.